The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/nau.24886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biofeedback treatment for children with non‐neurogenic voiding dysfunction: A systematic review and meta‐analysis

Abstract: Background Children's non‐neurogenic voiding dysfunction (NVD) is a syndrome characterized by lower urinary tract symptoms (LUTs) because of the inability to relax the external sphincter. Patients with NVD always suffer from urinary tract infections (UTI), incontinence, constipation. The aim of this study is to assess the efficacy of biofeedback treatment for children's NVD. Methods PubMed, Embase, Cochrane library database were searched for all relevant studies. Two independent reviewers decided whether to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Combined pharmacotherapy and standard urotherapy might be necessary for children with more severe DV and those with incontinence episodes [18]. Biofeedback-based PFMT has been recommended as the best noninvasive treatment for children with DV among the various available treatment approaches [1,6,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined pharmacotherapy and standard urotherapy might be necessary for children with more severe DV and those with incontinence episodes [18]. Biofeedback-based PFMT has been recommended as the best noninvasive treatment for children with DV among the various available treatment approaches [1,6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional voiding (DV) in children may result in lower urinary tract symptoms (LUTS), such as urgency, frequency, urinary incontinence, and difficulty in urination. High post-void residual (PVR) urine volume, vesicoureteral reflux (VUR), and recurrent urinary tract infection (UTI) may develop in children with severe DV, which can lead to renal function deterioration in the absence of appropriate treatment [1]. Detrusor overactivity (DO) is the most common urodynamic finding in children with DV, including high voiding detrusor pressure, recurrent UTI, bilateral VUR, and bowel dysfunction [2].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review revealed that biofeedback is effective in alleviating UTI symptoms or constipation. Moreover, biofeedback can improve postvoid residual and electromyography during voiding and has a longer-term effect [ 46 ].…”
Section: Treatmentmentioning
confidence: 99%